“Kabulok Komad Quartet Card” Learning Media: Student Interest and Learning Outcomes in Science - Wahyuni, Sri; Hanif, Muhammad; Sudarmiani, Sudarmiani (Journal Evaluation in Education (JEE), 2026)
Purpose of the study: This study examines the effectiveness of the “Kabulok Komad Quartet Card” learning media in improving students’ learning interest and learning outcomes in science (IPAS) learning at the elementary school level.Methodology: A quantitative approach was employed using a quasi-experimental posttest non-equivalent control group design. The participants consisted of 22 fourth-grade students at Elementary School 01 Nambangan Lor, Madiun City, divided into an experimental group (n = 11) that utilized the Kabulok Komad Quartet Card learning media and a control group (n = 11) that used conventional textbook-based learning media. Data were collected using a learning interest questionnaire and a learning outcomes test, then analyzed through descriptive statistics and independent sample t-tests at a 0.05 significance level.Main Findings: The results reveal that students in the experimental group demonstrated significantly higher learning interest and learning outcomes compared to those in the control group. The t-test results indicate a significant difference in learning interest (t = 5.358, p < 0.05) and learning outcomes (t = 5.194, p < 0.05) between the two groups. These findings suggest that the Kabulok Komad Quartet Card learning media is effective in creating an engaging, contextual, and student-centered learning environment.Novelty/Originality of this study: This study provides empirical evidence that integrating local cultural content through game-based learning media can enhance both affective and cognitive aspects of learning in elementary science education.